If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x)(x + 3) = 28 Reorder the terms: x(3 + x) = 28 (3 * x + x * x) = 28 (3x + x2) = 28 Solving 3x + x2 = 28 Solving for variable 'x'. Reorder the terms: -28 + 3x + x2 = 28 + -28 Combine like terms: 28 + -28 = 0 -28 + 3x + x2 = 0 Factor a trinomial. (-7 + -1x)(4 + -1x) = 0Subproblem 1
Set the factor '(-7 + -1x)' equal to zero and attempt to solve: Simplifying -7 + -1x = 0 Solving -7 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -1x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -1x = 0 + 7 -1x = 0 + 7 Combine like terms: 0 + 7 = 7 -1x = 7 Divide each side by '-1'. x = -7 Simplifying x = -7Subproblem 2
Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4Solution
x = {-7, 4}
| -5x+21=5x+2+6x-13 | | 4u=28 | | 7+3x+6=7x-5+5x | | 12x-40+7x+23=90 | | 12x-4x+136=12x+76 | | 21p^2-49p-42=0 | | x-8=90 | | 3(8+1)+6= | | 6.9=8.4-0.5x | | (x^2+x-20)(14x^2-3x-2)=0 | | -2(3k)=15 | | 6.9=8.4-0.5 | | 2y-x=-20 | | 3(10+1)+6= | | 7w+20=11w-20 | | f(x)=(2/3*3.1416x^6)^2 | | 51a^3-34a= | | 20p=-14+19p | | 4n^2+20n-56=0 | | -2x-5x-8=3x-8 | | 2x^6-4x^5-30x^4=0 | | 18.09-2n=-1.6-7.7n-12.57 | | 2/811/8x | | M+7+m-5=6(1+3m)-2(1+8m) | | 10a^2-8a= | | 3(v+3)-7v=24 | | -13d-16=-11d | | f(x)=4/3*3.1416x^2 | | 5X+6+2X=15 | | 3(v+3)-7v=2r | | f(x)=4/3*πx^2 | | -2m-19m+12=-20-17m |